ANALISIS WACANA CERPEN “LAUT MENGAMBIL CINTAKU” KARYA JEMMY PIRAN (SEBUAH TINJAUAN REFERENSI) - Hilmatun Nafis; Kitra Asoka Pradestania; Sumarlam (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
This study examines the references in the short story "Laut Mengambil Cintaku" by Jemmy Piran. The data in this study are in the form of speech or dialogue in short stories in which there are grammatical aspects, namely references. The source of the data in this research is one of the collections of short stories from Jawa Pos entitled "Laut Mengambil Cintaku"  by Jemmy Piran. This study used a qualitative descriptive method, and used listen and note method in collecting data. The data analysis method used in this study is agih method. The results of data analysis showed that the form of referential markers in the short story "Laut Mengambil Cintaku"  by Jemmy Piran includes 1) persona reference (first person reference, second person reference, and third person reference), 2) demonstrative reference (time-indicating pronouns and place-indicating pronouns), and 3) comparative reference. Keywords: reference, short story, discourse analysis